Increasing Productivity of Creative Industry MSMEs in the MEA Era by Utilizing Appropriate Technology (TTG): Peningkatan Produktifitas UMKM Industri Kreatif di Era MEA dengan Pemanfaatan Teknologi Tepat Guna (TTG) - Budi Gunawan; Sri Mulyani; Fajar Nugraha (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
In the MEA era, Indonesia and nine other ASEAN countries had the same opportunity to take advantage of integrated markets in one region. Because it is already in force, there is no other choice for people in ASEAN countries, including the business world, both large and micro, small and medium business (MSME) segments, in addition to being prepared to face the ASEAN open market. If MSMEs are placed in the market freely, their survival will be determined by the market, and with its various limitations, it will certainly be difficult to compete with business actors who are part of the global conglomerate network. For this reason, support and assistance from all elements are needed, both the government and academics in improving the competitiveness of MSMEs to developments in this open market arena. One of the SMEs engaged in the creative industry is "Tyara Craft" UKM which utilizes waste material, namely "corn cobs" to be turned into handicrafts that have economic value. This UKM is a developing UKM with a workforce of 6 people. This UKM established in 2017 with a total turnover of 156 million per year. These SME products are handicraft items from corn cobs, such as pendants, rings, table chairs, frames, tissue boxes, etc. The purpose of this activity is: increasing the productivity of creative industry SMEs that produce handicrafts from waste materials, namely corn cobs, by utilizing appropriate technology, namely sanding machines and cutters. The implemented method is divided into three stages; (1) the design and manufacture of TTG, (2) training on the use of TTG, and (3) workshops to increase the expertise of workers in the use of TTG. The results of this activity are; (1) increasing UKM productivity, (2) increasing UKM expertise, (3) increasing sales turnover with increasing production volume. Abstrak Di era MEA, Indonesia dan sembilan negara ASEAN lain memiliki kesempatan yang sama untuk memanfaatkan pasar yang terintegrasi dalam satu kawasan. Karena sudah berlaku, tidak ada pilihan lain bagi masyarakat di negara-negara ASEAN, termasuk dunia usaha, baik besar maupun segmen usaha mikro, kecil, dan menengah (UMKM), selain harus siap menghadapi ASEAN open market. Apabila UMKM ditempatkan di pasar secara bebas, kelangsungan hidupnya akan ditentukan oleh pasar, dan dengan berbagai keterbatasan yang dimilikinya tentu akan kesulitan bersaing dengan pelaku usaha yang menjadi bagian dari jaringan konglomerasi global. Untuk itu diperlukan dukungan dan bantuan dari semua elemen, baik pemerintah maupun kalangan akademisi dalam meningkatkan daya saing UMKM bisa berkembang di arena pasar terbuka ini. Salah satu pelaku UKM yang bergerak dalam industri kreatif adalah UKM “Tyara Craft” yang memanfaatkan bahan limbah yaitu ‘bonggol jagung’ untuk dirubah menjadi barang kerajinan yang mempunyai nilai ekonomis. UKM ini merupakan UKM yang sedang berkembang dengan tenaga kerja berjumlah 6 org. UKM ini berdiri sejak tahun 2017 dengan total omset per tahun 156 juta. Produk UKM ini adalah barang-barang kerajinan dari bahan bonggol jagung seperti lampu gantung, cincin, meja kursi, pigura, tempat tisu dsb. Tujuan dari kegiatan ini adalah: meningkatkan produktifitas UKM industri kreatif yang memproduksi barang kerajinan dari bahan limbah, yaitu bonggol jagung, dengan memanfaatkan teknologi tepat guna yaitu mesin pengamplas dan pemotong. Metode pelaksanaan dibagi dalam tiga tahap; (1) perancangan dan pembuatan TTG, (2) pelatihan penggunaan TTG, dan (3) workshop peningkatan keahlian tenaga kerja dalam pemanfaatan TTG. Hasil kegiatan ini adalah; (1) peningkatan produktifitas UKM , (2) peningkatan keahlian UKM, (3) peningkatan omset penjualan dengan meningkatnya volume produksi.